2006
DOI: 10.1101/gad.1422606
|View full text |Cite
|
Sign up to set email alerts
|

Histone modification-dependent and -independent pathways for recruitment of checkpoint protein Crb2 to double-strand breaks

Abstract: Cellular responses to DNA damage involve the relocalization of checkpoint proteins to DNA double-strand breaks (DSBs). The fission yeast checkpoint mediator protein Crb2, a homolog of mammalian 53BP1, forms ionizing radiation-induced nuclear foci (IRIF). The IRIF formation by Crb2 requires histone H2A C-terminal phosphorylation and H4-K20 methylation. However, the relevance of Crb2 relocalization is uncertain, because neither histone modification is required for a checkpoint response. Here we show that these h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
256
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(284 citation statements)
references
References 56 publications
24
256
1
3
Order By: Relevance
“…In Schizosaccharomyces pombe, histone H4-K20 methylation is not required for viability but controls the recovery time after DNA damage induced by irradiation (Sanders et al 2004;Du et al 2006). In essentially the same experiment as done in yeast, we examined the response of wild-type and mutant flies to g-irradiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Schizosaccharomyces pombe, histone H4-K20 methylation is not required for viability but controls the recovery time after DNA damage induced by irradiation (Sanders et al 2004;Du et al 2006). In essentially the same experiment as done in yeast, we examined the response of wild-type and mutant flies to g-irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…While the methyl marks are dispensable for viability, they show a weak phenotype in DNA damage response (Sanders et al 2004;Du et al 2006). This aspect of H4K20 methylation has been lost in Drosophila.…”
Section: Discussionmentioning
confidence: 99%
“…Expressing the budding yeast HO endonuclease in the presence of a 24-nucleotide (nt) HO recognition sequence inserted at the arg3 locus (arg3THO-site) on fission yeast chromosome 1 resulted in a persistent DSB and eventual cell death (Du et al 2003(Du et al , 2006. The fact that a mutation of the HO recognition sequence renders the cell resistant to continuous HO expression suggests that no other sequences can be efficiently cut by HO in the fission yeast genome (Li et al 2012).…”
mentioning
confidence: 99%
“…51 Further analyses have demonstrated that Crb2 IRIF formation is mediated by the Crb2 Tudor domain. 52 Crb2 is able to recognize H4K20 methylation and γH2AX simultaneously through the Tudor domain and the BRCT domain, respectively. 53 A subsequent study demonstrated that dimethylated H4K20, and not H3K79me, contributes to the relocation of 53BP1 to sites of DNA DSB, and established that 53BP1 and Crb2 proteins bind directly to dimethyl lysine H4K20.…”
Section: Chromatin Remodeling Activities During Dna Repairmentioning
confidence: 99%
“…Alternatively, the BRCT domains of these proteins can recruit PI3Ks proteins to regulate their activity and, as a consequence, to facilitate downstream signaling. 52,61 Histone H3K79 methylation is also important for the response to DNA damage caused by UV. 62 In mammalian cells, histone H3K79 methylation may also participate in the recruitment of 53BP1 through its double Tudor domain.…”
Section: Recognition and Signal Amplification Of Dna Damagementioning
confidence: 99%